Carbon Footprint of Semi-Mechanical Sago Starch Production - Mega Ayu Yusuf (Journal of Ecological Engineering, 2019)
Indonesia is the country with the greatest potential for sago in the world. This research is intended to determine the carbon footprint of sago starch produced from a semi-mechanical process. The calculation was carried out using the LCA approach with the system boundary of cradle to gate. The process steps were carried out in a combination of manual work and diesel-driven engines. The inventory data on material, energy input flows and emissions were obtained from 3 samples of typical medium-scale semi-mechanical sago mills. It was found that the carbon footprint of the sago produced from semi-mechanical processes was 37.9±0.6 kgCO2eq per 1 ton of dried sago starch. Further analysis shows that 62% of the carbon footprint comes from the extraction stage and 38% from the transportation. It can be estimated that the amount of greenhouse gas emissions from the semi-mechanical sago starch production in Indonesia for 2018 reached around 2,617,639 kg CO2eq.